1985
DOI: 10.1007/bf02424564
|View full text |Cite
|
Sign up to set email alerts
|

The Lansing effect and age-mediated changes in genetic parameters

Abstract: The influence of variation in age of grandparents upon the heritability of two metric characters has been studied in the guppy (Poecilia reticulata) and Drosophila melanogaster. In both cases effects on heritability paralleling those already demonstrated to occur with variation in parental age were found and may be regarded as examples of Lansing effects.Analysis of components of variance of sternopleural bristle number in Drosophila suggest that the genotypic variance for this character is increased in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Medawar, 1952;Williams, 1957;Szillard, 1959;Orgel, 1963;Comfort, 1964;Curtis, 1966;Sinex, 1974;Kirkwood, 1977;Sacher & Hart, 1978;Kirkwood & Holliday, 1979). Beardmore and Shami (1985) found that the genotypic variance for sternopleural bristle number in Drosophila had increased in the progenies of older parents, largely as a consequence of an increase in additive genetic variance. Beardmore et al (1975) showed earlier that the heritability of previously mentioned quantitative traits increases with advance in parental age, which had been also demonstrated in other metric characters, such as caudal fin ray number in the guppy fish (Beardmore & Shami, 1976), as well as in a twin study of total finger ridge count in man (Lints, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Medawar, 1952;Williams, 1957;Szillard, 1959;Orgel, 1963;Comfort, 1964;Curtis, 1966;Sinex, 1974;Kirkwood, 1977;Sacher & Hart, 1978;Kirkwood & Holliday, 1979). Beardmore and Shami (1985) found that the genotypic variance for sternopleural bristle number in Drosophila had increased in the progenies of older parents, largely as a consequence of an increase in additive genetic variance. Beardmore et al (1975) showed earlier that the heritability of previously mentioned quantitative traits increases with advance in parental age, which had been also demonstrated in other metric characters, such as caudal fin ray number in the guppy fish (Beardmore & Shami, 1976), as well as in a twin study of total finger ridge count in man (Lints, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…44 An effect of parental age on traits in the offspring has been found for skeletal characters in mice, 45 for egg size, bristle number, wing size, development time and other characters in Drosophila, 46 for the number of generations of asexual progeny in the protozoan Paramecium, 16 and for the heritability of some traits in fish, 47 Drosophila 48 and man. 49 The incidence of many human hereditary traits depends on the age of the parents.…”
Section: Parental-age Effectsmentioning
confidence: 98%
“…Earlier, Beardmore and Shami suggested that inherited chromatin changes could be responsible for the changes with increasing parental and grandparental age in the heritability of various metric characters in the guppy and in Drosophila. 47 Although at present it is difficult to know whether particular parental-age effects are the result of genetic, epigenetic, or environmental factors, there is one category, Lansing effects, that seems particularly likely to have an epigenetic basis. Lansing effects are parental age effects that are transmissible, cumulative and reversible.…”
Section: Parental-age Effectsmentioning
confidence: 98%
“…A puzzling set of observations is that the heritahiliiy of some traits also increases with age; this has been found for the number of caudal fin rays in the fish Poecilia reticulata [39], for sternopleural bristle number in Dro sophila [39,40], and for finger ridge counts in man [41], With most characters, the vari ation which depends on parental age is at tributable more to maternal than to paternal age, but the age of the father can certainly affect some characters in the offspring [33,38],…”
Section: Parental Age Effects and Lansing Effectsmentioning
confidence: 99%
“…However, Beardmore and Shami [39] tenta tively suggested that chromatin changes causing alterations in gene expression may have been responsible for the increased heritability of metric characters which they found with increasing parental and grandparental age in Drosophila and P. reticulata. We believe that there are indeed several fea tures in their data and that from other stud ies of parental age effects and Lansing ef fects which support an interpretation based on epigenetic inheritance.…”
Section: Epigenetic Changes and Parental Age Effectsmentioning
confidence: 99%